Pengaruh Pengalaman dan Tekanan Ketaatan Terhadap Audit Judgment - Kadir, Nila; Hasibuan, David H.M (Institut Bisnis dan Informatika Kesatuan, 2017)
Each company is required to provide information on the financial statements in accordance with applicable standards that have been set. Therefore, the company needs further examination in order to meet accountability to investors and creditors and the public that may affect the valuation of the company. Such informations should be useful and presented appropriately and accurately for users of financial statements. To fulfill this obligation, the company requires the services of a third party audit of the so-called independent auditor as the party in charge of examining and giving an opinion on the report presented by management. In recent decades, audit failure cases are rare and have led to the crisis of confidence regarding the inability of the accounting profession in the audited financial statements. The emergence of this crisis is indeed justified, because quite a lot of financial statements of a company that received an unqualified opinion, but it went bankrupt after the opinion was issued. To prevent the occurrence of cases of failure of the audit, the auditor is required to be professional. Professionalism has become a critical issue for the accounting profession because it can describe the performance of the accountant. Professionalism of auditors can be reflected by the accuracy of the auditor in making judgments in the audit assignment. Many factors affect the performance of an auditor in making audit judgments, among other experiences and compliance pressure. The purpose of this study was to determine the effect of experience and stress adherence to audit judgment. Research was conducted on public accounting firms in Bandung. Respondents are auditors working in the public accounting firms in Bandung. Of the 40 questionnaires distributed, there were 33 questionnaires were returned and could be processed for further testing. The analytical method used in this research is multiple linear regression analysis and processed using SPSS 16. Results of research on the influence of experience and stress adherence to audit judgment shows that the experience had no effect on audit judgment, while the pressure obedience significantly effecting on audit judgment. Audit experience does not affect the judgment audit because the auditor with different experiences will have the same audit consideration. Auditor with experience <1 year, 1-5 years, 6-10 years or> 10 years will have the same audit consideration when obtaining evidence, and the same information anyway. Compliance pressure affects the audit because the auditor's judgment tends to follow orders from superiors so that would affect the auditor's judgment. An auditor who is under pressure will tend to take the safe road, not at risk, and tend to be dysfunctional. It also indicates that the auditor does not have the courage to disobey the orders of their superiors and the client's desire to change audit firm even if the instruction is not appropriate. Surely few are willing to take risks to find another job and losing clients as a consequence against the orders of superiors and clients wishes improper deviated from professional standards.